Supporting trade finance for trade expansion and diversification in West Africa - Marc Auboin (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
A joint study by the WTO and IFC established that the low share of trade supported by trade finance (25%) in the four largest economies of West Africa (Nigeria, Côte d'Ivoire, Ghana and Senegal) was a major constraint in further expanding and diversifying trade flows and trade integration. Raising trade finance use in the region to the African average of 40% of trade flows, would result in an increase in the region's trade flows of 8% annually, 80% in ten years.
Keywords: 330